Caso Kuntur Wasi: sociedad aeroportuaria Kuntur Wasi SA y Corporación América SA con la República del Perú (caso CIADI ARB/18/27) - Rey de Castro Alarco, Álvaro (2020)
The present article examines in a preliminary perspective the Kuntur Wasi Case, which is actually been under an Arbitral Tribunal in ICSID. It is focused in the probable perspectives that the present case may take under an analysis that centres in the Peru-Argentina BIT and its Public International Law norms.